W(5): Wobbling Mode in the Framework of the X(5) Model - Bonatsos, Dennis; Lenis, D.; Petrellis, D.; Terziev, P. A. (HNPS Advances in Nuclear Physics, 2020)
Using in the Bohr Hamiltonian the approximations leading to the Bohr and Mot- telson description of wobbling motion in even nuclei, a W(5) model for wobbling bands, coexisting with a X(5) ground state band, is obtained. Separation of vari ables is achieved by assuming that the relevant potential has a sharp minimum at 70, which is the only parameter entering in the spectra and B(E2) transition rates (up to overall scale factors). B(E2) transition rates exhibit the features expected in the wobbling case.